Firm turnover in the export market and the case for fixed exchange rate regime - Masashige Hamano; Francesco Pappadà (Bank of Finland, 2020)
This paper revisits the case for flexible vs. fixed exchange rate regime in a two-country model with firm heterogeneity and nominal wage rigidity under incomplete financial markets. Dampening nominal exchange rate fluctuations simultaneously stabilizes the firm turnover in the export market. When firms are homogeneous and low productive, the fixed exchange rate regime dominates the flexible one because it reduces the fluctuations in labor demand arising from entry and exit of exporters following a demand shock. We also show that an alternative regulation policy in the export market does not rule out the possible adoption of a managed floating regime.
URN:NBN:fi:bof-202001071001
Keywords: F32; F41; E40; 330; monetary policy; exchange rate regime; firm heterogeneity